Diet composition of redfish (Sebastes sp.) during periods of population collapse and massive resurgence in the Gulf of St. Lawrence - Brown-Vuillemin, Sarah; Chabot, Denis; Nozères, Claude; Tremblay, Réjean; Sirois, Pascal; Robert, Dominique (Frontiers in Marine Science, 2022)
Redfish (Sebastes mentella and S. fasciatus) are back at spectacular record high levels in the Gulf of St. Lawrence (GSL) and the effects of this massive resurgence on other components of the food web remain largely unknown. To better understand the trophic implications of the surging redfish biomass within the GSL ecosystem, 3,690 stomachs containing food were collected during two periods: one characterised by low redfish abundance (1993–1999) and the other during a period of record abundance (2015–2019). Taxonomical analysis of stomach contents from individuals of different sizes from three subareas of the GSL was carried out to determine diet composition during both periods. Zooplankton represented the main prey category for small redfish (< 20 cm), which was driven by a predation on amphipods, mostly Themisto sp. in North-East Gulf, in the 1990s and on copepods of the genus Calanus in the deep channels and euphausiids in North-East Gulf in the 2010s. Themisto sp. still dominated the diet of medium (20–30 cm) redfish in the 1990s while the copepods were predominant during the 2010s. Shrimp consumption increased with redfish size and two species were particularly important in large redfish diet (≥ 30 cm) during both periods: pink glass shrimp (Pasiphaea multidentata), mostly in the Laurentian Channel and northern shrimp (Pandalus borealis), especially in North-East Gulf. Redfish predation on shrimp represents a major concern for the dynamics of the northern shrimp which supports a valuable fishery in the GSL but has been declining in abundance since several years. Piscivory was observed in large redfish diet, with capelin (Mallotus villosus) being the major fish prey in the 1990s and redfish (cannibalism) in the 2010s, suggesting density-dependent control at high density of small redfish. By presenting a detailed overview into the redfish diet composition and its temporal variability, the present study offers a first look into the possible future trophic impacts of a resurging groundfish in the GSL ecosystem.